Turning the Spotlight on Meat-borne Viral Diseases - Das, Ujjal; Bordoloi, Devika; Bharadwaj, Anish; Shome, Arijit (International Journal of Bio-resource and Stress Management, 2025)
Food borne diseases are and have been an ongoing menace all over the globe. Meat or meat products constitute a major food in almost all classes of people worldwide. Unfortunately, meat when contaminated, serves as a major source and carriers of a number of viral diseases. Noroviruses (NoV), Rotaviruses (RV) and Hepatitis A and E viruses are among the major viruses transmitted by meat and its products causing serious conditions like acute gastroenteritis and hepatitis when consumed without treating and cooking properly. Other viral diseases like MERS, SARS, COVID-19, and Avian Influenza also possess the possibility of transmission through food (meat). Although treatment and prophylaxis for prevention of some of these diseases are available, but due to cosmopolitan nature of the viruses, it is easy for anyone to get afflicted with the disease. It is noteworthy that some of the aforementioned disease(s) have been speculated to have zoonotic implications as well. Control, prevention and strict microbiological testing of meat and meat products right at the level of the source still remain the best method in preventing these diseases. However, for maintenance of good public health standards, it is very important for us to acknowledge not only the food borne bacterial and parasitic diseases, but also the viral pathogens and the diseases they cause. This review highlights some of the important food-borne viral diseases from the etiological, pathological, clinical and prevention cum prophylactic point of view.